Energy Efficiency in Colombia: Trends and Challenges (2014)
Sustainable energy is important to achieve development and welfare of population because it is a key to analyse how the countries use their energy as an element that strengthens productive activities from environmental protection perspective. This study seeks to determine the progress in sustainable energy in Colombia for the last decade by analysing trends and challenges of energy efficiency through some indicators to establish results, achievements, gaps and barriers in the context of the institutional and policy framework. Results of this analysis demonstrated that Colombia has achieved significant advances in this field recognizing the need to increase energy efficiency especially in the power, industrial and transport sectors.